August Strindberg's novels - Språkbanken Text (University of Gothenburg, 2024)
August Strindberg's novels and dramas have been published as a national edition, Nationalupplagan av August Strindbergs samlade verk, by Stockholm University and Norstedts.

The material is not proofread by the editors, and may thus contain minor errors and deviations from the printed volumes. For more information about the publication of the Collected Works, see the homepage of the Strindberg project. See also the frequency and word explanation query.

August Strindbergs romaner och dramer har utgivits som Nationalupplagan av August Strindbergs samlade verk av Stockholms universitet och Norstedts.

Materialet i databaserna är ej korrekturläst av utgivarna, smärre felaktigheter och avvikelser från de tryckta volymerna kan därför förekomma. För mer information om utgivningen av Samlade Verk, se Strindbergsprojektets hemsida. Se även frekvens- och ordförklaringssökning.
August Strindbergs romaner
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik